The Effect Of Temperature And Humidity On Swallow's Nest Production In Engkuni Pasek Village, West Kutai Regency (Jurnal Peternakan Lingkungan Tropis, 2021)
The research aims to determine the effect of temperature and humidity on the production of swallow's nest in Engkuni Pasek village, West Kutai regency, East Kalimantan. The research was conducted in March 2020, in Engkuni Pasek Village, the parameters measured included temperature and humidity measurements to determine the production of swallow's nest. The results showed that the temperature and humidity swallow's nest to the production of swallow's nest, namely in building A the temperature ranges from 25- 32 are known oC, building B 25-31 oC, building C 25-34 oC, building D 25-34 oC, building E 25-32 oC and building F 27-30 oC. building A has humidity ranging from 72-78%, building B 88-25%, building C 91-99%, building D 76-86%, building E 77-99% and building F 82-99%. The average yields of swallow nest production per year in building A are 327.5; building B, namely 195; building C, namely 285; building D, namely 165; building E is 637.5 and building F is 187.5. where it can be seen that the highest swallow production results are in building E, namely 637.5 which has a high enough humidity of ± 95% and a temperature of ± 32 oC while the lowest production is in building D which is 165 which has good humidity ± 86% and a temperature of ± 34 oC. From the research it can be concluded that temperature and humidity have no effect on the production of swallow's nest.
Keywords: Array; Array; Array; Array